ANALISIS YURIDIS SOSIOLOGIS DALAM TRADISI BEKASAI PADA MASYARAKAT MELAYU SAMBAS - Kharan Rizvi Aryu; Marluwi Marluwi; Suhardiman Suhardiman (Al-Usroh, 2025)
This research is motivated by the widespread shift in local cultural values due to modernization, which threatens the existence of unique traditions in Malay communities. This raises questions regarding the cultural resilience and legal standing of the bekasai tradition in Kartiasa Village, Sambas. The purpose of this study is to describe the implementation of the bekasai tradition in wedding processions, analyze its position from a juridical-sociological perspective, and formulate a pattern of harmonization with Islamic law and national law. The method used is empirical legal research with a juridical-sociological approach, employing data collection techniques such as observation, interviews, and documentation. Data were analyzed qualitatively based on theories of legal pluralism and structural functionalism. The results show that bekasai is a herbal scrub practice accompanied by prayers for safety as a symbol of self-purification traditionally required by custom. Juridically, this tradition is a living law that is recognized de facto by the community and does not conflict with Islamic sharia because it contains elements of benefit (maslahah). In conclusion, the bekasai tradition is an instrument of social cohesion and a guardian of cultural identity that needs formal legal protection through regional regulations to ensure the sustainability of the cultural rights of the Sambas Malay community.